The Implementation of Demonstration Method to Students Learning Outcomes and Interests on Colloid Materials at Class XI Science of SMA Negeri 1 Kasimbar - Megawati Megawati; Suherman Suherman; Purnama Ningsih (Jurnal Akademika Kimia, 2020)
This research aims to examine the demonstration method on chemistry learning through colloid materials to learning achievement and interest of students at class XI Science of SMA Negeri 1 Kasimbar. This research was a true experimental design with pretest-posttest control group design. Sampling was carried out based on special considerations (purposive sampling) with 21 students in class XI science 2 as a sample of experimental class and 21 students of class XI science 1 as control class. This research instruments were a learning achievement test and questionnaire. Data was analyzed through descriptive statistical analysis, namely test questionnaire data, as well as inferential statistical analysis to test the hypothesis using two-party t-test. Analysis of questionnaire data of students’ learning interests showed that the experimental class was in the agree to category with a percentage of 78.05% while the control class was in the agree category with a percentage of 60.63%. Therefore, it can be concluded that the demonstration method in chemistry learning on colloidal material affects the learning achievement learning interest of students class XI Science of SMA Negeri 1 Kasimbar.